KERJASAMA GURU DAN ORANG TUA DALAM PEMBELAJARAN DARING DI ROUDLOTUL ATHFAL MUSLIMAT NU 15, SUKUN KOTA MALANG - Sayyidatul Musyarrofah; Muhammad Hanif; Ika Anggraheni (UNISMA, 2021)
In march 2020, the world, including Indonesia, was shocked by the 2019 Corona Virus Diasease (Covid 19) or better known as the corona virus, which forces everyone in educational institutions to edjust learning so that the learning process continues, even though the place, time, and cnditions are uncertain. This time at the Roudlotul Athfal Muslimat Nu 15 institution, learning that is appropriate to the current pandemic situation and conditions, as one of the learning activites given to students to be done at home with their parents. in this study, it will beexplaiined how the cooperation of teachers at Roudlotul Athfal Muslimat NU 15 inducludes planning, implemention and supporting and inhibiting factors in online learning. Researchers used a qualitative approach. And the type of case study research. Data collection teachniques used are in-dept interviews, observation and documentation. The results of the study show that the cooperation of teachers and perents in online learning has been going quite well.